203k views
3 votes
Explain how to solve 3x - 1 = 1 - 3x ​

User JibW
by
4.3k points

2 Answers

2 votes

Step 1: Simplify both sides of the equation.

3

x

1

=

1

3

x

3

x

+

1

=

1

+

3

x

3

x

1

=

3

x

+

1

Step 2: Add 3x to both sides.

3

x

1

+

3

x

=

3

x

+

1

+

3

x

6

x

1

=

1

Step 3: Add 1 to both sides.

6

x

1

+

1

=

1

+

1

6

x

=

2

Step 4: Divide both sides by 6.

6

x

6

=

2

6

x

=

1

3

User Dan Pritts
by
5.3k points
1 vote
X= 1/3, I hope this help
Explain how to solve 3x - 1 = 1 - 3x ​-example-1
User Therealrootuser
by
4.3k points